Attending Krsna’s Image: Caitanya Vaisnava Murti-seva as Devotional Truth, by Kenneth R. Valpey - Dwyer, Graham (Religions of South Asia, 2008)
Attending Krsna’s Image: Caitanya Vaisnava Murti-seva as Devotional Truth, by Kenneth R. Valpey. Abingdon, Oxon and New York: Routledge, 2006. xiv + 225 pp., £80 (hb). ISBN 0-415-38394-3.